Back Cover Image. (28th January 2021) - Li, Nan; Tang, Haitao; Wu, Liang; Ge, Haitao; Wang, Yurong; Yu, Honglin; Zhang, Xiuli; Ma, Jimei; Gu, Harvest F.
Abstract : The cover image is based on the Review Chemical constituents, clinical efficacy and molecular mechanisms of the ethanol extract of Abelmoschus manihot flowers in treatment of kidney diseases by Nan Li et al., https://doi.org/10.1002/ptr.6818 . Abstract : The cover image is based on the Review Chemical constituents, clinical efficacy and molecular mechanisms of the ethanol extract of Abelmoschus manihot flowers in treatment of kidney diseases by Nan Li et al., https://doi.org/10.1002/ptr.6818 .